Easy and fast procedure to isolate, purify and immortalize DNA fragments for allelic ladders construction. (December 2015) - Burgos, G.; Restrepo, T.; Ibarra, A.; Gaviria, A.; Machado, G.; Mora, C.; Lizarazo, R.
Abstract: Allelic ladders are essential quality standards in forensic casework analysis with STRs. These are obtained by mixing individual genotypes, however, when alleles are obtained from heterozygous individuals, they cause allelic unbalance in the ladder mix and dependence upon original DNA extracts availability. In this work alleles were amplified and separated from heterozygous state by agarose or polyacrylamide gels after electrophoresis. Target alleles were recovered by gel puncturing and then reamplified; subsequent dilutions (10 −3 –10 −4 ) of these amplificates were used as new templates for PCR with fluorolabelled primers. This strategy was successfully used to obtain balanced allelic ladders for mini STRs D10S1248 and D14S1434 tetra nucleotides which are part of NC01 (Non Codis) triplex. It is also worth noticing that this procedure could also be used to isolate new or mutant alleles that are to be sequenced.